Mutant NPM1-Regulated FTO-Mediated m6A Demethylation Promotes Leukemic Cell Survival via PDGFRB/ERK Signaling Axis - Xiao, Qiaoling; Lei, Li; Ren, Jun; Peng, Meixi; Jing, Yipei; Jiang, Xueke; Huang, Junpeng; Tao, Yonghong; Lin, Can; Yang, Jing; Sun, Minghui; Tang, Lisha; et al. (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) with nucleophosmin 1 (NPM1) mutations exhibits distinct biological and clinical features, accounting for approximately one-third of AML. Recently, the N6-methyladenosine (m6A) RNA modification has emerged as a new epigenetic modification to contribute to tumorigenesis and development. However, there is limited knowledge on the role of m6A modifications in NPM1-mutated AML. In this study, the decreased m6A level was first detected and high expression of fat mass and obesity-associated protein (FTO) was responsible for the m6A suppression in NPM1-mutated AML. FTO upregulation was partially induced by NPM1 mutation type A (NPM1-mA) through impeding the proteasome pathway. Importantly, FTO promoted leukemic cell survival by facilitating cell cycle and inhibiting cell apoptosis. Mechanistic investigations demonstrated that FTO depended on its m6A RNA demethylase activity to activate PDGFRB/ERK signaling axis. Our findings indicate that FTO-mediated m6A demethylation plays an oncogenic role in NPM1-mutated AML and provide a new layer of epigenetic insight for future treatments of this distinctly leukemic entity.